Analytical solution for active pressure of narrow backfills considering arching effect. Issue 1 (15th June 2020) - Ghobadi, Sahar; Shahir, Hadi
Abstract : Purpose: The purpose of this paper is to study the distribution of active earth pressure in retaining walls with narrow cohesion less backfill considering arching effects. Design/methodology/approach: To this end, the approach of principal stresses rotation was used to consider the arching effects. Findings: According to the presented formulation, the active soil pressure distribution is nonlinear with zero value at the wall base. The proposed formulation implies that by increasing the frictional forces at both sides of the backfill, the arching effect is increased and so, the lateral earth pressure on the retaining wall is decreased. Also, by narrowing the backfill space, the lateral earth pressure is extremely decreased. Originality/value: A comprehensive analytical solution for the active earth pressure of narrow backfills is presented, such that the effects of the surcharge and the characteristics of the stable back surface are considered. The magnitude and height of the application of lateral active force are also derived.